PENGARUH BRAND EXPERIENCE DAN KESADARAN MEREK TERHADAP LOYALITAS MEREK PADA PENGGUNA PRODUK SMARTPHONE SAMSUNG DI DESA PELANG KECAMATAN KEMBANGBAHU KABUPATEN LAMONGAN - Putra Manuel, Mahadi; Nur Azizah, Luluk (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
This research aims to determine the influence of Brand Experience and Brand Awareness on Brand Loyalty in users of Samsung brand smartphone products in Pelang village, Kembangbahu subdistrict, Lamongan Regency. Analysis of the data that has been collected for this research will be processed using quantitative methods. The population in this study were residents of Pelang village, Kembangbahu subdistrict, Lamongan district, users of Samsung brand smartphone products aged over 17 years. In this research, researchers used data collection techniques using a Non-Probability Sampling system with Purposive Sampling Technique (Sample with Certain Criteria). The sample used in this research was 106 respondents. The data was analyzed using SPSS version 25. The data analysis technique used multiple linear regression analysis, classical assumption test, t-test, f-test and coefficient of determination, previously the results of the questionnaire data were tested for validity and reliability. Based on the results of the analysis and discussion, it can be concluded from the two independent variables studied that Brand Experience and Brand Awareness have a partially significant influence on Brand Loyalty. This relationship produces the Multiple Linear Regression equation as follows: Y = 5.913 + 0.257X1 + 0.492X2 + e From calculations using Multiple Linear Regression and a significance level of 5% or 0.05, the calculated F value is 163.301 > from the F table of 3.08 and the significance is 0.000 < 0.05. This means that in this research the Brand Experience (X1) and Brand Awareness (X2) variables simultaneously and significantly influence the Brand Loyalty variable (Y).